THU0121 Ultrasound in the assessment of carpal tunnel syndrome in patients with rheumatoid arthritis. (15th June 2017) - Matteo, A Di; Filippucci, E; Smerilli, G; Draghessi, A; Gasparini, S; Incorvaia, A; Carlo, M Di; Grassi, W
Abstract : Background: Carpal tunnel syndrome (CTS) is one of the most frequent extra-articular manifestations of rheumatoid arthritis (RA). Ultrasound (US) has proven to represent a reliable tool for the diagnosis of CTS [1]. However, its role in the diagnosis of CTS in patients with RA has been poorly investigated. Objectives: The aim of this study is to evaluate the US findings at carpal tunnel level in a cohort of patients with RA, focusing on those with a clinical diagnosis of CTS. Methods: Patients with RA fulfilling the ACR/EULAR 2010 classification criteria were consecutively enrolled. The diagnosis of CTS was made according to the American Academy of Neurology practice parameter for CTS [2]. The MSUS assessment was carried out using a MyLab Twice (Esaote SPA) US system working with a 18–22 MHz linear probe. The power Doppler (PD) frequency was set between 7.5 and 11.3 MHz. The following grey scale (GS) US parameters were assessed at the carpal tunnel level: cross-sectional area (CSA) of the median nerve at the carpal tunnel inlet (at the level of the pisiform and scaphoid bones), presence of flexor tenosynovitis and palmar radio-carpal synovitis (both in GS and PD), presence of crystal macro-aggregates and marked bone profile irregularities. The median nerve was considered enlarged if its CSA was more than 12 mm 2 . We evaluated the presence of intra-neural PD signals at the carpal inlet and scored its entity (0=no PD signal, 1=one single vessel within median nerve, 2=two or three single or two confluent vessels and 3=more than three single or more than two confluent vessels). PD was considered "positive" if grade 1 or more was found. Results: We included 40 RA patients. CTS was diagnosed in 19 out of 80 wrists (23.8%) and in 13 out of 40 RA patients (32.5%). Enlarged median nerve was found in 3 out of 19 wrists with CTS (15.8%) and in 6 out of 61 wrists without CTS (9.8%). Flexor tenosynovitis was found in 7 out of 19 wrists with CTS (36.8%) and in 5 out of 61 wrists without CTS (8.2%). Palmar radio-carpal synovitis was found in 2 out of 19 wrists with CTS (10.5%) and in 3 out of 61 wrists without CTS (4.9%). Crystal macro-aggregates were not detected in any of the scanned wrists. Marked bone profile irregularities were found in 2 out of 19 wrists with CTS (10.5%) and in 14 out of 61 wrists without CTS (23%). Positive intra-neural PD was found in 9 out of 19 wrists with CTS (47.4%) and in 9 out of 61 wrists without CTS (14.7%). Conclusions: These preliminary results suggest that MSUS could be a useful tool in the diagnosis of CTS also in patients with RA. Intra-neural PD and flexor tenosynovitis were the most frequently MSUS abnormalities detected in RA patients with CTS. The inflammatory involvement of the tendinous and joint structures which are part of the carpal tunnel could lead to median nerve compression and CTS symptoms and should be considered in the MSUS assessment of CTS. References: McDonagh C, Alexander M, Kane D. The role of ultrasound in the diagnosis and managment of carpal tunnel sindrome: a new paradigme. Rheumatology (Oxford). 2015 Jan;54(1):9–19.doi: 10.1093/rheumatology/keu275. Practice parameters for carpal tunnel syndrome (summary statement). Report of the quality standards subcommittee of the American Academy of Neurology. Neurology 1993;43:2406–9. Disclosure of Interest: None declared